APPLICATION OF THE INTERDISCIPLINARY RELATIONS FOR HIGHER EDUCATION QUALITY ASSURANCE - Svitlana Zaskaleta; Natalia Buglay (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article highlights the issue of ensuring the quality of higher education through the prism of the use of interdisciplinary links on the example of the study of historical disciplines and foreign languages. The analysis of the legal framework, as well as the scientific literature made it possible to identify effective ways to ensure the quality of higher education. One of them is the application of the principles of interdisciplinary relations. The implementation of the interdisciplinary approach is considered as a promising method for the professional training of students of the Faculty of History with the use of knowledge of a foreign language. It is proposed to create integrated programs, teaching professional disciplines in English. It is recommended to offer students English literature In the context of the interdisciplinary approach, the integration of professional components using the skills of linguistic literacy is considered. The concept of interdisciplinary research is based on the premise that concepts and facts are not studied in isolation from each other. Implementation of the disciplinary approach is considered as a promising method for professional training of students for the application of knowledge in other disciplines. The European vector of higher education development is determined by the high level of requirements for the specialist, which necessitates the search for effective ways to ensure the quality of higher education. One of the directions of updating the learning process is the integration of educational material from different disciplines, namely: historical disciplines and foreign language. To apply the principle of interdisciplinary links, it is important to use the CLIL approach in foreign language classes. The teaching of professional disciplines in English is relevant today in domestic universities, as it is an important factor in increasing prestige, internationalization and improving the quality of professional training. When creating integrated programs to enhance the independent cognitive activity of students of the Faculty of History, it is important to recommend students to English-language literature. The use of interdisciplinary connections allows students of the Faculty of History to discover their creative potential and develop as a person.